Aspects of bird diversity and ecology in ”Riscani” forest park, Chisinau municipality - Cîrlig, Tatiana (Acta et Commentationes Exact and Natural Sciences, 2023)
Our study has been focused on the diversity and ecology of birds in the “Rîșcani” forest park, Chișinău municipality. The scientific investigations were conducted between April and August 2022. We inventoried 52 species of birds with uneven distribution in the territory included in this study. The greatest diversity was found in forest areas subjected less to the anthropogenic impact. Vegetation management practices applied in the park and the expansion of recreational areas are disruptive factors for bird species, especially for their breeding population. Of the avifauna of the area, 50 species, or 96.2% of identified birds are included in the lists of the International Union for Conservation of Nature (IUCN), and 44 species, or 84.6%, are also included in the lists of the Bern Convention.